Epidemiology and Haemato-Biochemical Changes in Mange Infested Camels - Pandya, Nidhi R; Mandali, Ghanshyam C; Dave, Keshank M; Raval , Sunant K (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Mange in camel, also named as sarcopticosis is defined as an extremely contagious skin disease characterized by scab formation, pruritic  dermatitis, thickening and corrugation of skin and hair loss. A total of 21 positive cases of mange infestation were selected from those  presented at the Veterinary Clinical Complex of the College, in Anand and from surrounding villages. The affected camels were divided  into 3 groups, viz., B, C, D each group comprised of 7 camels, while seven healthy camels in group A served as control. The maximum  prevalence of sarcoptic mange among infected animals was found in the age group of >6 years (52.38 %), followed by 4-6 years (38.09  %) and in
Keywords: Camel; Haemato-biochemical alterations; Mange infestation